Changes in the physical activity of acute stroke survivors between inpatient and community living with early supported discharge: an observational cohort study. Issue 4 (December 2016) - Kerr, A.; Rowe, P.; Esson, D.; Barber, M.
Abstract: Objective: To describe and compare patterns of physical activity among stroke survivors during their hospital stay and community living with early supported discharge. Design: Observational cohort study of physical activity before and after early supported discharge. Setting: UK National Health Service stroke units and participants' homes. Participants: Forty-one stroke survivors with a mean age of 69 (standard deviation 11) years, and a median Modified Rivermead Mobility Index of 33.5 [interquartile range (IQR) 25.8 to 35.3]. Main outcome measures: The primary outcome measures were time spent in sitting/standing/walking and number of steps taken, as recorded by a physical activity monitor. Results: There were statistical differences ( P < 0.001) for all categories of physical activity. After early supported discharge to the community, participants took more than twice the number of steps median 474 (IQR 189 to 773) vs. 1193 (IQR 512 to 2856), median difference 636 [95% confidence interval (CI) 262 to 931] and spent more than double the time in standing [median 51 (IQR 22 to 128) minutes vs. 100 (IQR 51 to 178) minutes, median difference 28 (95% CI 11 to 68)] compared with their hospital stay. Conclusion: Community living with early supported discharge promoted higher levels of physical activity in medically stable stroke survivors. The near-doubling of activity may serve as a guideline for what is achievable during stroke rehabilitation. Clinical Trial Registration: Number UKCRN 15472.